2013
DOI: 10.1371/journal.pone.0065187
|View full text |Cite|
|
Sign up to set email alerts
|

The Early Stage Formation of PI3K-AMPAR GluR2 Subunit Complex Facilitates the Long Term Neuroprotection Induced by Propofol Post-Conditioning in Rats

Abstract: Previously, we have shown that the phosphoinositide-3-kinase (PI3K) mediated acute (24 h) post-conditioning neuroprotection induced by propofol. We also found that propofol post-conditioning produced long term neuroprotection and inhibited the internalization of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor GluR2 subunit up to 28 days post middle cerebral artery occlusion (MCAO). However, the relationship between PI3K with AMPA receptor GluR2 subunit trafficking in propofol post-conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Recent studies also have shown that propofol can induce formation of the P13K-AMAR GluR2 sub-unit complex, affect the NF-kB/p53 signalling pathway, inhibit neuron-specific CREB dephosphorylation and reduce the internalization of the AMPAR GluR2 sub-unit [37][38][39][40]. In addition, propofol may reduce the metabolism of neurons, delay the energy exhaustion and maintain the activity of Ca 2+ /Mg 2+ ATPase and Na + /K + ATPase, which is necessary for homeostasis of electrolytes in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also have shown that propofol can induce formation of the P13K-AMAR GluR2 sub-unit complex, affect the NF-kB/p53 signalling pathway, inhibit neuron-specific CREB dephosphorylation and reduce the internalization of the AMPAR GluR2 sub-unit [37][38][39][40]. In addition, propofol may reduce the metabolism of neurons, delay the energy exhaustion and maintain the activity of Ca 2+ /Mg 2+ ATPase and Na + /K + ATPase, which is necessary for homeostasis of electrolytes in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“… 60 61 In addition, several chemicals, drugs, and neurotrophic factors have been reported to activate PI3K ( Table 1 ). 62 63 64 65 66 67 68 …”
Section: Pi3k Pathway Activation To Enhance Recovery or Regeneration mentioning
confidence: 99%
“…The increase of intracellular Ca 2+ causes a cascade of events (proteases/endonucleases activation and production of free radicals that shatter cell membranes) leading to cell death through the induction of apoptosis [84] . On the basis of such observations, it is possible to say that the maintenance of the synaptic exposure of Ca 2+ -impermeable AMPARs may play a protective activity against cerebral ischemia/reperfusion injuries [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] . This ability resulted to be particularly evident in the brain of hibernating mammals that are able to tolerate severe hypoxia conditions [86] , very probably via the up-regulation of GluR2 that being responsible for low intracellular Ca 2+ levels is consequently responsible for the greater resistance to ischemia-induced neuronal damages .…”
Section: Role Of Neuroprotective Factors During Cerebral Ischemiamentioning
confidence: 99%
“…Parallel to this capacity, also the persistent neuronal production in some adult brain areas constitutes a potential capacity for self-repairing processes following ischemic cerebral attack [89] . Indeed, after ischemia, neuronal proliferation was up-regulated several fold, and rapidly half of post-ischemic precursors develop neuronal phenotype in some hippocampal fields [85] , that have shown to be the more ischemia-susceptible limbic areas [90] .…”
Section: Role Of Neuroprotective Factors During Cerebral Ischemiamentioning
confidence: 99%